Reviews. Issue 1 (1st July 2019) - Martinez, Nicolas; Curtis, Neal
Why Comics? From Underground to Everywhere, Hillary Chute (2017) New York: Harper, 464 pp., ISBN 978-0-06247-680-7, h/bk, US$40EC Comics: Race, Shock and Social Protest, Qiana Whitted (2019) New Brunswick: Rutgers University Press, 181 pp., ISBN 978-0-81356-631-3, p/bk, £25.50